Differential associations between obesity and behavioral measures of impulsivity. (1st December 2015) - Lawyer, Steven R.; Boomhower, Steven R.; Rasmussen, Erin B.
Abstract: A growing literature indicates that impulsivity is a fundamental behavioral process that underlies obesity. However, impulsivity is a multidimensional construct, which comprises independent patterns of decision-making that could be uniquely associated with obesity. No research to date has clarified whether obesity is differentially associated with specific behavioral aspects of impulsivity. This study examined whether obesity was differentially associated with patterns of decision-making associated with impulsivity—delay discounting, probability discounting, and response inhibition. Young adults (n = 296; 44.3% male) age 18–30 were recruited from the community with media advertisements. Participants completed a series of standard self-report measures of health outcomes and behavioral measures of delay discounting, probability discounting, and response inhibition individually in a laboratory. Associations between body mass index (BMI) and behavioral outcomes in the whole sample indicated that BMI was associated with age, delay discounting, and probability discounting, but not response inhibition. A logistic regression that included age, sex, and substance use as covariates found that delay discounting, but neither probability discounting nor response inhibition, was associated with obesity status. Sensitivity to delay, rather than response inhibition and sensitivity to uncertainty, may be the best correlate of obesity status in adults. These findings are relevant to our understanding of the fundamental behavioral processes associated with obesity. Highlights: We examine three behavioral measures of impulsivity in relation to body mass index. We determine what measure(s) of impulsivity are uniquely associated with obesity status. Understanding impulsivity process associated with obesity inform treatment. Obesity status is associated with delay discounting for monetary outcomes. Obesity status is not associated with probability discounting or response inhibition.